Relationships between material properties and microstructure-mechanical attributes of extruded biopolymeric foams - Agbisit, Roderick Nazario Malcaba (Kansas State University, 2007)
Material formulation and extrusion process parameters affect the foaming process in terms of expansion, cell nucleation, and resultant foam microstructure, which, in turn, control mechanical properties. This study utilizes non-invasive x-ray microtomography (XMT), in combination with mechanical testing and novel phase transition analysis techniques, to understand these complex relationships. The first part of this study provided significant insight into the deformation mechanism of extruded cornstarch foams. Microstructure features, including average cell diameter (2.07-6.32 mm), wall thickness (0.13-0.25 mm) and number density (18-146 cm-3), were measured. Microstructure had moderate to high correlations (|r| = 0.48 - 0.81) with mechanical properties, including compression modulus (2.2-7.8 MPa), crushing stress (42-240 kPa), number of spatial ruptures (2.6-3.6 mm-1), average crushing force (22-67 N) and crispness work (6.4-22 N-mm). The second part of this study investigated the effects of formulation, using model systems comprising of cornstarch, whey protein isolate (WPI) and sucrose, on phase transition behavior, and physical, microstructure and mechanical properties of extrudates. Increase in WPI led to greater specific mechanical energy (SME) and higher extrudate expansion. WPI had a foaming effect, which increased the cell number density accompanied by decrease in average cell diameter. Increase in sucrose led to lesser SME and lower expansion of extrudates. Contrary to expectations, phase transition properties (softening temperature, Ts, and flow temperature, Tf) were not good indicators of SME. The concluding part of this study investigated glass transition and rheological properties of cornstarch at different moisture contents (18-30% wet basis) using differential scanning calorimetry (DSC), phase transition analysis (PTA) and on-line slit-die rheometry. Glass transition temperature (Tg) (31.20 - 57.55 C) of extrudates decreased as moisture content increased. Ts (42.5 - 85.6C) and Tf (109 - 136C) also followed the same trend, and exhibited high correlations (r = 0.89 and 0.86, respectively) with Tg. These parameters were good estimates of phase transition properties of the complex and heterogeneous formulations. As expected, on-line rheological parameters, including flow behavior index, n (0.0438 - 0.304) and consistency coefficient, K (10,500 - 45,700 Pa-sn-1), were functions of in-barrel moisture, and were related to phase transition properties using WLF kinetics.
Keywords: Phase transition; Microstructure; Mechanical; Extrusion; Biopolymeric foams; Agriculture, Food Science and Technology (0359)